2014
DOI: 10.1016/j.ydbio.2014.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Lhx1 is required in Müllerian duct epithelium for uterine development

Abstract: The female reproductive tract organs of mammals, including the oviducts, uterus, cervix and upper vagina, are derived from the Müllerian ducts, a pair of epithelial tubes that form within the mesonephroi. The Müllerian ducts form in a rostral to caudal manner, guided by and dependent on the Wolffian ducts that have already formed. Experimental embryological studies indicate that caudal elongation of the Müllerian duct towards the urogenital sinus occurs in part by proliferation at the ductal tip. The molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 75 publications
3
60
0
Order By: Relevance
“…3D). This observation is reminiscent of Müllerian duct-specific Lhx1 mutant mice, which show impaired migratory activity in the tip regions (Huang et al, 2014). However, our mutant mice retained Lhx1 expression, which was confirmed by section immunostaining (Fig.…”
Section: Fig 5 (Right) Lhx1 Expression and Canonical Wnt Signaling supporting
confidence: 77%
See 3 more Smart Citations
“…3D). This observation is reminiscent of Müllerian duct-specific Lhx1 mutant mice, which show impaired migratory activity in the tip regions (Huang et al, 2014). However, our mutant mice retained Lhx1 expression, which was confirmed by section immunostaining (Fig.…”
Section: Fig 5 (Right) Lhx1 Expression and Canonical Wnt Signaling supporting
confidence: 77%
“…Thus, Müllerian duct elongation was dependent on the preformed Wolffian duct. Although Lhx1 in the Wolffian and Mül-lerian ducts is essential for Müllerian duct elongation (Huang et al, 2014;Kobayashi et al, 2005), the unaltered Lhx1 expression observed in both ducts of the mutant mice indicates that loss of Lhx1 expression is not the major cause of the Müllerian duct defects.…”
Section: Müllerian Duct Elongation Depends On the Preformed Wolffian mentioning
confidence: 91%
See 2 more Smart Citations
“…Research proves that the JNK can regulate downstream of the WNT signaling pathway, which is essential for the development of female reproductive ducts [30]. Other MDA candidate genes, such as LHX1, which also encodes for a transcription factor, participate in the period of mullerian duct formation [31]. And it is possible that PAX2 can adjust upstream of or in parallel with LHX1 and cooperatively regulate other factors in the development of the mullerian duct [22].…”
Section: Discussionmentioning
confidence: 99%